Returning Individual-Level Urgent or Emergent Research Results to Participants: The Project Baseline Health Study Experience - Neha Pagidipati; Brooke Heidenfelder; Lydia Coulter Kwee; Fatima Rodriguez; Ranee Chatterjee; Kishan S. Parikh; Michel G. Khouri; Jennifer Stiller; Julie Eckstrand; P. Kelly Marcom; Priyatham S. Mettu; Glenn J. Jaffe; et al. (American Journal of Medicine Open)
Background: Returning results to research participants is increasingly recognized as an ethical mandate, yet little is known about best practices to optimally communicate urgent or emergent results. Methods: We describe the development of and experience with a process to return results to participants in the Project Baseline Health Study (PBHS), which was a prospective observational cohort study of 2502 participants enrolled from 2017 to 2019 and followed through 2023. Urgent or emergent results were returned during or after the baseline visit from vital signs; clinical laboratory testing; and ocular, cardiovascular, and pulmonary imaging. Results: Among 2002 participants in this analysis, 39.7% had at least one urgent or emergent finding returned, representing a total of 1159 results returned over 3 years. The most commonly returned results were eye findings (n = 246), pulmonary nodules (n = 159), abnormal stress echocardiograms (n = 123), abnormal rest electrocardiograms (bradycardia) (n = 74), and lung parenchyma findings (n = 55). Participants with urgent or emergent incidental findings were older (mean [SD] 58.0 [16.2] years vs 48.0 [16.6] years) with a greater burden of cardiovascular, metabolic, or cancer comorbidities than those without urgent or emergent incidental findings. Conclusions: This report from the PBHS study is one of the first to describe a process to systematically return urgent or emergent results to research participants. This process led to the successful return of clinically important results to participants but also required significant time and effort from study clinicians and staff.